Produção de eritritol por leveduras cultivadas em meio contendo glicerol como fonte de carbono - Paula, Marília Santiago de Brito de (2017)
Erythritol is a polyol that is currently produced in biotechnological processes since chemical synthesis appears to be ineffective. It has numerous characteristics that make it interesting for the food industries like low calories, taste very similar to sucralose, safe for the consumption of diabetics and non-cariogenic. Microbial species, especially yeasts, are of great importance for the production of erythritol. In this work, thirty-two yeasts from the Collection of Cultures of Agricultural Microbiology (CCMA) were used for growth tests, carbon source consumption and erythritol production in media containing glycerol or glucose at 100g / L concentration. The results showed that of the thirty-two yeasts tested, three were more efficient in the production of erythritol: Candida rugosa CCMA 0371, and two strains of Yarrowia lipolytica CCMA 0242 and CCMA 0357. In addition to erythritol, the presence of mannitol and arabitol Both in glucose and glycerol, and glycerol is considered better than glucose for the production of erythritol, mannitol and also arabitol.